THE SPECIFICITY OF THE MINOR'S LIABILITY IN COMPARATIVE CRIMINAL LAW - Ana-Maria ROTĂRESCU (Challenges of the Knowledge Society)
Criminal liability, offense and punishment are the three pillars of criminal law and therefore the core of criminal law. In the absence of certainty as to criminal liability, the system of legal rules governing social relations, in order to protect them, would be seriously undermined, making it impossible to re-establish the broken legal order. Criminal liability is the most serious form of legal liability, since it occurs when the most important social values are harmed, social values that become legal values by virtue of the legislator's defense. One category of active subjects of a conflict - seen as a criminal legal relationship - is minors. The increasing number of crimes committed by minors has led to a criminal phenomenon among minors. The regulation of the criminal liability of minors is a constant in all legal systems, differing in terms of the age of criminal liability and the system of punishment applied by each State. Also, as we shall see, the criminal legislature in other countries has attached particular importance to the regulation of the criminal liability of minors by enacting special laws in this regard. The objective of the present research is to analyse the institution of criminal liability of minors in comparative criminal law in order to identify a solution that best suits the prevention of juvenile crime.